2017
DOI: 10.1080/14397595.2017.1332471
|View full text |Cite
|
Sign up to set email alerts
|

Safety and effectiveness of tacrolimus add-on therapy for rheumatoid arthritis patients without an adequate response to biological disease-modifying anti-rheumatic drugs (DMARDs): Post-marketing surveillance in Japan

Abstract: TAC is well tolerated and effective when used as an add-on to biological DMARDs in Japanese patients with RA who do not achieve an adequate response to biological DMARDs in a real-world clinical setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 34 publications
5
15
0
Order By: Relevance
“…A majority of patients in the present study took a dose of TAC ≤ 2 mg/d, with a mean dose of 1.6 mg/d at week 24. This result is similar to that reported in the TAC PMS study (mean, 1.3 mg/d) . In patients previously treated with bDMARDs, TAC at baseline dose‐dependently augmented the efficacy of add‐on ABT, and concomitant TAC at 3 mg/d demonstrated the maximum efficacy .…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…A majority of patients in the present study took a dose of TAC ≤ 2 mg/d, with a mean dose of 1.6 mg/d at week 24. This result is similar to that reported in the TAC PMS study (mean, 1.3 mg/d) . In patients previously treated with bDMARDs, TAC at baseline dose‐dependently augmented the efficacy of add‐on ABT, and concomitant TAC at 3 mg/d demonstrated the maximum efficacy .…”
Section: Discussionsupporting
confidence: 87%
“…That study found that elderly patients had a higher incidence of infection compared with non‐elderly patients, and that patients treated with ABT had a higher incidence of infection compared to those treated with other bDMARDs (8/99 patients: 8.1% vs 0.0%‐6.1%). However, among eight patients who experienced infection in this cohort, six were aged >70 years, and only one patient had a serious but reversible infection . Since TAC is a calcineurin inhibitor which suppresses the activation of T lymphocytes, and ABT is also an agent that inhibits T cell activation by binding to CD80/86 on the antigen‐presenting cell surface, one would expect the combined use of these agents to further increase the risk of infection.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Tacrolimus has been reported to be effective, and it shows an acceptable safety profile in RA patients with an inadequate response to csDMARDs, including methotrexate [6,7]. In addition, it has been suggested that add-on tacrolimus with bDMARDs may improve the clinical outcomes, even when patients show inadequate responses to bDMARDs with concomitant methotrexate [8][9][10]. These findings indicate that the use of tacrolimus may be one of the valuable options for patients with contraindications for or an inadequate response to bDMARDs and/or methotrexate.…”
Section: Introductionmentioning
confidence: 99%